EVALUASI PELAKSANAAN PROGRAM BEASISWA MISKIN (BSM-SMA/SMK) DI SMK ASSHODIQIYAH SEMARANG - Metalia Ulfah; Puji Astuti; Fitriyah . (Journal of Politic and Government Studies, 2013)
Poor scholarship program (BSM-SMA/SMK) originated from one of theeducational problems faced by Indonesian nation is still high dropout rates and thelow participation of the poor to education. The purpose of this program is to helpstudents from poor families to obtain educational services, as well as to lower thedropout rate. The purpose of this study is to investigate the implementation of theprogram in SMK Asshodiqiyah BSM-SMA/SMK Semarang and to investigate theimpact of the program. This type of research is a descriptive study. The researchmethod used was qualitative. Informant retrieval technique using purposivesampling technique. Data collection techniques used were interviews anddocument research penilitian Results showed that: (1) The implementation is donein accordance with the provisions contained in the program guidelines issued byKemendikbud BSM-SMA/SMK. However BSM-SMA/SMK programimplementation in the city, especially in vocational Asshodiqiyah can not be saidto be successful because the fund has not been able to improve access to educationfor the poor. Besides these schools still like to hold such levies building fees,tuition, books peket Lessons with a number of very burdensome parents ofstudents who come from my family can not afford to acquire education akase. (2)The purpose of this program is to help the poor gain access to education services,but the benefits or impact of the program can not be fully felt by the parents ofstudents rec